Female versus Male Entrepreneurship within Europe - Ardelean, Dorina; Pribac, Loredana (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Entrepreneurship is a topic much debated and analyzed by many research institutions and organizations. In recent years, the total number of entrepreneurs has been increasing significantly, female entrepreneurship being the one that has increased a lot. In this study, we are going to present and analyze the results of studies conducted at European level regarding the comparative evolution of male versus female entrepreneurship. The main conclusion that emerges from the analysis of the results obtained is that the number of women entrepreneurs is almost equal to that of men entrepreneurs in many European countries.